Data visualization : causes and risk factors of death / Amirah Mohd Yusof and Jiwa Noris Hamid - Mohd Yusof, Amirah; Hamid, Jiwa Noris (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Human mortality data visualization can assist higher-up organizations in the medical profession or governmental departments in dealing with death trends, which advise that different countries take suitable measures to minimize their death rate. The objectives of this study are to analyze the retrieved datasets on mortality causes and its risk factors that effect the death rate, to construct a dashboard and visualize the death rate and the relationship between death rate and death causes and also risk factors of the death and lastly, to assess the dashboard's performance in visualizing the relationship of death rate based on the causes and also the risk factors that lead to the death. Therefore, data visualization is needed in give insight for higher up to make a decision. The data set for this project is obtain from Kaggle and Our World In Data website. Firstly, the planning and preliminary phase will be conducted to gather information about project area. The second phase is analysis phase where the process data preparation for the retrieved data set will be going in acquire cleaning data set. The next phase for the project will be development phase. This phase include the process of constructing data visualization and designing dashboard and lastly testing phase. The finding of this project will help in minimizing the death rate in the country. The higher up could get insight from this data visualization for the country and make differences with other country death rate in reducing the number for their country. This analysis shows how important geographical and economic factors are in affecting the death patterns.